Asphyxiated Female and Male Newborn Piglets Have Similar Outcomes With Different Cardiopulmonary Resuscitation Interventions - Kim, Seung Yeon; Shim, Gyu-Hong; O'Reilly, Megan; Cheung, Po-Yin; Lee, Tze-Fun; Schmölzer, Georg M. (Frontiers in Pediatrics, 2020)
Background Male newborns have a greater risk of poor cardiovascular and respiratory outcomes compared to females. The mechanisms associated with the “male disadvantage” remains unclear. We have previously shown no difference between male and female newborn piglets during hypoxia, asphyxia, resuscitation, and post-resuscitation recovery. However, it is unknown if there are differences in resuscitation outcomes between males and females during different cardiopulmonary resuscitation techniques. Intervention and measurements Secondary analysis of 184 term newborn mixed breed duroc piglets (1-3 days of age, weighing 2.0 (0.2) kg) from seven different studies, which were exposed to 30-50 min of normocapnic hypoxia followed by asphyxia until asystole. This was followed by cardiopulmonary resuscitation. For the analysis, piglets were divided into male and female groups, as well as resuscitation technique groups (sustained inflation, 3:1 compression-to-ventilation ratio, or asynchronous ventilations during chest compressions). Cardiac function, carotid blood flow, and cerebral oxygenation were continuously recorded throughout the experiment. Main results Regardless of resuscitation technique, there was no significant difference between males and females in the number achieving return of spontaneous circulation (ROSC) [95/123 (77%) vs. 48/61 (79%)], the time to achieve ROSC [112 (80-185) sec vs. 110 (77-186) sec], and the 4-hour survival rate [81/95 (85%) vs. 40/48 (83%)]. Levels of the injury markers interleukin (IL) -1ß, IL-6, IL-8, and tumour necrosis factor-α in frontoparietal cortex tissue homogenates were similar between males and females. Conclusions Regardless of resuscitation technique, there was no significant effect of sex on resuscitation outcome, survival, and hemodynamic recovery in asphyxiated newborn piglets.